Selenium-enriched probiotics improve hepatic protection by regulating pro-inflammatory cytokines and antioxidant capacity in broilers under heat stress conditions - Khan, Alam Zeb; Khan, Imdad Ullah; Khan, Shakirullah; Afzal, Samreen; Hamid, Mohammad; Tariq, Muhammad; Haq, Ikram Ul; Ullah, Naimat; Khan, Mumtaz Ali; Bilal, Shahid; Huwang, Kehe; Liu, Ran (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: High ambient temperature in poultry is a challenging and fatal stress among environmental factors. It affects the production quality, damages the liver, and increases mortality in broilers. The present study is focused to explore appropriate utilization of Selenium (Se) as a feed additive in broiler chickens against high temperature. Materials and Methods: Day-old male broiler chickens (Ross 308) (n = 200) were grouped according to the supplements used in their basal diets such as: corn-soybean basal diet as control (Con), a basal diet containing sodium selenite, basal diet with probiotics, and a basal diet containing selenium-enriched probiotics (SP). At the end of the experimental period of 42 days, the liver was isolated and was used to determine the antioxidant capacity through a spectrophotometer. Inflammatory and anti-inflammatory cytokines production in the liver was measured through a real-time polymerase chain reaction. Results: Hepatic analyses revealed the decreased level of malondialdehyde, whereas glutathione, glutathione peroxidase (GSH-Px), and superoxide dismutase levels were increased in the SP group. Furthermore, supplementation of SP significantly up-regulated the mRNA expression of glutathione peroxidase 1 (GPx1), GPx4, IL6, and IL10 and down-regulated the expression of pro-inflammatory cytokines. Conclusion: It is thus concluded that SP as a potential nutritive supplement may facilitate hepatic protection by suppressing hepatic oxidation, inflammation, and necrosis during the high ambient temperature of summer. J. Adv. Vet. Anim. Res., 6(3): 355-361, September 2019